Interview with Dr. Prem Bhandari - Khattri, Man Bahadur; Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2025)
Dr. Prem Bhandari is a distinguished social scientist and a member of the International Advisory Board of Dhaulagiri Journal of Sociology and Anthropology (DJSA). Dr. Bhandari was born and raised in rural Nepal, where he began his academic pursuits. His educational journey continued across Kathmandu, Chitwan, Thailand, and the USA, covering diverse fields of study including biology, agricultural economics, rural development planning, and rural sociology and demography. Dr. Bhandari completed his PhD in Rural Sociology and Demography from the Pennsylvania State University, USA. His research interests are broad, spanning fertility, migration, rural livelihoods, population health, and the socio-economic and cultural determinants of social change, with a particular focus on Nepal and South Asia. His current research focuses on factors contributing to profitability in agritourism, visitor attractions, and activity diversification in agritourism. His academic career spans several prestigious institutions, including Tribhuvan University, Nepal; the University of Alberta, Canada; the University of Michigan; and the University of Maryland Eastern Shore. In Nepal, Dr. Bhandari has contributed to applied research in social science through the Institute for Social and Environmental Research-Nepal (ISER-N). In addition to his roles in teaching, research, and Extension, he has been deeply engaged in national and international research collaborations, hosting and participating in conferences, mentoring scholars in Nepal and the U.S., and serving as an editor for academic journals. His positive attitude, warm heart, simplicity, and willingness to share his valuable time, experiences, and skills, and his contribution through publishing research articles in food security, migration, and research methods for the DJSA have encouraged us to get to know him better. We believe his life trajectory will serve as a profound source of inspiration for emerging scholars to shape their own lives. We are thankful and extend our sincere gratitude to Dr. Bhandari for accepting the proposal for a written interview, in which he has generously and thoughtfully engaged.